PENGARUH POSISI GERAKAN SHALAT DHUHA 8 RAKAAT TERHADAP TEKANAN DARAH SISTOLIK DAN DIASTOLIK SERTA DETAK JANTUNG PADA MUSLIMAH LANSIA DI PANTI BINA LANSIA KOTA BINJAI 2021 - SRI RIZQI SIHALOHO; ELMAN BOY (JURNAL ILMIAH SIMANTEK, 2023)
Duha prayer is a strong place of refuge in the face of adversity, when praying a person will feel calm and relaxed to stimulate the anterior pituitary, inhibiting the adrenal cortex so that blood pressure decreases. Prayer movements can cause a decrease in heart rate and can result in decreased cardiac output, which in turn will cause a decrease in systolic pressure, whereas a decrease in diastolic pressure will result in a decrease in peripheral resistance. the purpose of this study was to determine the effect of the position of the 8 rakaat dhuha prayer on systolic and diastolic blood pressure and heart rate in elderly Muslim women. This type of research uses a quasi-experimental research study with a one group post test only research design which aims to determine the effect of the 8-rakaat dhuha prayer movement on systolic and diastolic blood pressure and heart rate in elderly Muslim women. Sampling using a total sampling of 37 people. Results: The results of the heart rate before the dhuha prayer (80.5±7.9), the heart rate after the dhuha prayer (75.8±7.1), systolic blood pressure before the dhuha prayer (148.1±17.9), diastolic blood pressure before dhuha prayer (90.2 ± 20.1), systolic blood pressure after dhuha prayer (141.7 ± 16.2), diastolic blood pressure after dhuha prayer (82.2 ± 9.6). Prayer movements have an effect on decreasing blood pressure and heart rate in the elderly. There is a significant effect on the position of the 8 rakaat dhuha prayer movement on systolic and diastolic blood pressure and heart rate in elderly Muslim women.